2020
DOI: 10.1002/capr.12346
|View full text |Cite
|
Sign up to set email alerts
|

Emotion‐focused therapy for symptoms of generalised anxiety in a student population: An exploratory study

Abstract: A global survey from the World Health Organization finds that approximately one-third of screened third-level students meet criteria for a mental disorder in the past twelve months, with major depressive disorder having the highest prevalence followed by generalised anxiety disorder (GAD;Auerbach et al., 2018). Likewise, within student counselling services (SCS), there is a growing concern globally

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…All 11 studies examined clients' experiences of helpful aspects of EFT, while seven studies featured difficult but helpful aspects of EFT (Angus & Kagan, 2013; Elliott, 2013; Hibbs et al, 2020; Nødtvedt et al, 2019/ Stiegler et al, 2018/Stige et al, 2021; O'Connell Kent et al, 2020; Steinmann et al, 2017; Timulak et al, 2017), and six studies featured experiences of unhelpful aspects of EFT (Hibbs et al, 2020; MacLeod et al, 2012; Nødtvedt et al, 2019; O'Connell Kent et al, 2020; Steinmann et al, 2017; Stiegler et al, 2018; Stige et al, 2021; Timulak et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All 11 studies examined clients' experiences of helpful aspects of EFT, while seven studies featured difficult but helpful aspects of EFT (Angus & Kagan, 2013; Elliott, 2013; Hibbs et al, 2020; Nødtvedt et al, 2019/ Stiegler et al, 2018/Stige et al, 2021; O'Connell Kent et al, 2020; Steinmann et al, 2017; Timulak et al, 2017), and six studies featured experiences of unhelpful aspects of EFT (Hibbs et al, 2020; MacLeod et al, 2012; Nødtvedt et al, 2019; O'Connell Kent et al, 2020; Steinmann et al, 2017; Stiegler et al, 2018; Stige et al, 2021; Timulak et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This meta‐category was based on findings reported in five out of 11 meta‐analysed studies and referred to the clients' experiences of feeling heard and/or being understood by the therapist. One client described how her therapist “was very understanding… she was kind of the first person who I felt like really understood what I was going through” (O'Connell Kent et al, 2020; p. 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Broadening treatment choice is not only in line with the service-user-centered ethos embraced by public health service providers such as the service where the here presented study took place, but it also has the potential to positively influence outcomes (Swift et al, 2018). The present study, which builds on initial open trials (O’Connell Kent et al, 2021; Timulak et al, 2017), is a step in the development of an alternate psychological treatment for GAD, namely emotion-focused therapy (EFT) for GAD (Timulak & McElvaney, 2018).…”
mentioning
confidence: 99%
“…Initial studies conducted in primary care and student counseling settings examined the adaptation of EFT for GAD using an open trial format and showed promising results (O’Connell Kent et al, 2021; Timulak et al, 2017). The present study was intended to contribute to the further assessment of EFT as a viable alternative to an established treatment of GAD (CBT) as provided in a public primary care setting.…”
mentioning
confidence: 99%